A Textual Analysis of Cohesion and Coherence in the Background Sections of Theses by Preservice Madrasah Ibtidaiyah Teachers - Kamil, Achmad Muchamad; Lestari, Citra Rizky (Universitas Islam Lamongan, 2025)
This study examines the coherence and cohesion aspects of the background sections of theses written by preservice Madrasah Ibtidaiyah teachers. Using a descriptive qualitative approach, five theses were purposively selected from official university repositories. Analysis was conducted using a discourse framework of cohesion and coherence to examine how students structured and connected ideas in their writing. The results indicate that students are good at using cohesive devices, particularly conjunctions and anaphoric references. However, substitution and ellipsis are rarely used, resulting in suboptimal language efficiency. In terms of coherence, most texts have a logical flow; however, the connections between ideas are weak, and the development of ideas is often uneven. These findings suggest that although students possess basic competencies in academic writing, they still require more focused instruction on rhetorical style and text organization. This study has practical implications for improving academic writing pedagogy and curriculum development in teacher education programs, particularly in the context of Islamic higher education.